Valuation Dimension of Ring Zn Using Python - S., Arifin; H., Garminia (International Journal of Engineering and Technology, 2018)
We counting valuation dimension of the ring Zn. Recently, Ghorbani and Nazemian introduced the notion of a valuation dimension of a commutative rings that measures of how far a commutative ring deviates from being valuation. They have proven that an Artinian ring has finite valuation dimension. Therefore, the ring Zn has finite valuation dimension. In this article, some methode and a tool to determine the valuation dimension of the ring Zn will be provided using Python.